2023
DOI: 10.3390/cimb45070334
|View full text |Cite
|
Sign up to set email alerts
|

Update in Molecular Aspects and Diagnosis of Autoimmune Gastritis

Abstract: Recent studies have advanced our understanding of the pathophysiology of autoimmune gastritis, particularly its molecular aspects. The most noteworthy recent advancement lies in the identification of several candidate genes implicated in the pathogenesis of pernicious anemia through genome-wide association studies. These genes include PTPN22, PNPT1, HLA-DQB1, and IL2RA. Recent studies have also directed attention towards other genes such as ATP4A, ATP4B, AIRE, SLC26A7, SLC26A9, and BACH2 polymorphism. In-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…H. pylori-positive patients with corpus atrophic gastritis seem to have high levels of anti-parietal cell antibodies, which decrease significantly after H. pylori eradication. The destruction of parietal cells by H. pylori-related inflammation may lead to the exposure of molecular patterns of the ATPase pump H+/K+ and consequently the production of anti-parietal cell antibodies as a consequence of a cross reaction between molecular antigens of the bacterium and molecular patterns of the ATPase pump H+/K+; this is more likely to occur in genetically predisposed subjects with specific MHC class II haplotypes [16] (Table 1). Two recent case reports showed that H. pylori-related gastritis ultimately transitioned into AAG; furthermore, they showed that the progression of AAG caused a spontaneous disappearance of H. pylori infection as a consequence of the worsening of the gastric atrophy [17].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori-positive patients with corpus atrophic gastritis seem to have high levels of anti-parietal cell antibodies, which decrease significantly after H. pylori eradication. The destruction of parietal cells by H. pylori-related inflammation may lead to the exposure of molecular patterns of the ATPase pump H+/K+ and consequently the production of anti-parietal cell antibodies as a consequence of a cross reaction between molecular antigens of the bacterium and molecular patterns of the ATPase pump H+/K+; this is more likely to occur in genetically predisposed subjects with specific MHC class II haplotypes [16] (Table 1). Two recent case reports showed that H. pylori-related gastritis ultimately transitioned into AAG; furthermore, they showed that the progression of AAG caused a spontaneous disappearance of H. pylori infection as a consequence of the worsening of the gastric atrophy [17].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Iwamuro M, Curr Issues Mol Biol 2023 [16] Helicobacter pylori may play a role in the induction/exacerbation of AAG.…”
Section: References Findingmentioning
confidence: 99%
“…Autoimmune gastritis is a persistent inflammation of the stomach arising from the autoimmune system's erroneous targeting and subsequent destruction of gastric parietal cells, resulting in reduced gastric acid secretion and vitamin B12 deficiency [54][55][56]. Reduced gastric acid production leads to elevated levels of gastrin.…”
Section: Neuroendocrine Tumors In Autoimmune Gastritismentioning
confidence: 99%
“…This immune-mediated process is driven by the production of autoantibodies against the H+/K+-ATPase (proton pump) and intrinsic factor, leading to the malabsorption of vitamin B12 and causing pernicious anemia. Over time, the progressive loss of gastric acid-producing cells results in a hypo-or achlorhydric environment within the stomach [1][2][3].…”
Section: Introductionmentioning
confidence: 99%